Risk factors for non-cancer health events in patients with head and neck squamous cell carcinoma - Ryu, C. H.; Roh, J. -L.; Kim, S. -B.; Lee, S. -W.; Choi, S. -H.; Nam, S. Y.; Kim, S. Y. (OXFORD UNIV PRESS, 2013)
Background: Cancer progression and non-cancer-related morbidities can affect the quality of life and survival of patients with head and neck squamous cell carcinomas (HNSCC). The aim of this study was to investigate the risk factors for the development of non-cancer health events (NCHEs) in HNSCC. Patients and methods: The study involved 465 previously-untreated patients with HNSCC diagnosed between 2005 and 2009 at the Asan Medical Center. Non-cancer-associated morbidity was defined as readmission after treatment of HNSCC due to non-cancer-related causes. NCHEs were defined as the occurrence of non-cancer-associated morbidity or mortality. The incidence and risk factors for NCHEs were analyzed. Results: During the median follow-up of 47.6 months, non-cancer morbidity and mortality occurred in 83 (17.8%) and 25 patients (5.4%), respectively. Thirteen patients (52%) died from non-cancer-related causes with no previous admission for non-cancer causes. Multivariate analysis showed that the incidence of NCHEs was significantly associated with a Charlson comorbidity index >= 1 and stage III/IV disease (P < 0.001). Conclusions: Patients with comorbidities and advanced diseases may be at higher risk of NCHEs. Because NCHEs are sometimes life-threatening, every effort should be made to avoid unexpected non-cancer-associated mortality in the HNSCC patients.
Keywords: 2ND PRIMARY TUMORS; OROPHARYNGEAL CANCER; HUMAN-PAPILLOMAVIRUS; COMPETING RISKS; CHEMOTHERAPY; SURVIVAL; ALCOHOL; SMOKING; IMPACT